Collateral soft tissue release in primary total knee replacement. (January 2014) - Goudie, Stuart; Deep, Kamal
Abstract The aim of this study was to assess the rate of collateral soft tissue release required in navigated total knee arthroplasty (TKA) to achieve an intra-operative coronal femoral tibial mechanical axis (FTMA) in extension of 0 ± 2°. The primary outcomes assessed were post-operative coronal plane alignment and rate of collateral soft tissue release. The secondary outcomes were range of motion, function, patient satisfaction, and complication rates at one-year follow-up. This is a prospective study of 224 knees. No exclusions were made on the basis of pathology or severity of deformity. Pre-operative FTMA ranged from 27° valgus to 25° varus (mean: −4.5° SD 7.6). Soft tissue release was carried out in 5 of 224 knees (2.2%). Post-operative weight-bearing radiological FTMA ranged from 7° valgus to 8° varus (mean: −0.4° SD 2.5°). Two hundred and ten knees (96%) were within 0 ± 5° of neutral. At one year, median maximum flexion was 100° (IQR 15°) and extension was 0°; mean post-operative Oxford Knee Score had improved from 42 to 23; and 91% of patients were satisfied or very satisfied, with only 2% being dissatisfied. We have found that in the vast majority of cases, including those with large pre-operative coronal deformity in extension, good outcomes in terms of coronal alignment, range of movement, function and patient satisfaction can be achieved.